2022
DOI: 10.1186/s12866-022-02672-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of carbapenem-resistant Klebsiella pneumoniae ST15 of producing KPC-2, SHV-106 and CTX-M-15 in Anhui, China

Abstract: Background: It is well known that carbapenem-resistant Klebsiella pneumoniae (CRKP) has become a more problematic public health issue due to its widespread spread worldwide. In China, ST11-type CRKP is the most prevalent CRKP, but ST15-type CRKP, a recently prevalent high-risk clone, has emerged widely throughout China, posing a serious public health risk. Therefore, we conducted an epidemiological of an outbreak of ST15 CRKP of producing CTX-M-15, KPC-2 and SHV-106 in a tertiary hospital in An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 65 publications
0
4
1
Order By: Relevance
“…However, this study found that the MIC of imipenem was 2-16mg/L, lower than that of meropenem (4-32mg/L), which may be related to the presence of membrane protein genes (OmpK35/36/37). The antibiotic susceptibility and resistance genes of ST15-type strains reported in the study also differ from previous reports ( Hu et al., 2013 ; Han et al., 2021 ; Zhao et al., 2022 ). Most ST15 OXA-232-producing CRKP strains in previous studies co-produce CTX-M-15 , KPC-2 and NDM-1 , while our strains carry three more AMR genes, including CTX-M-1 , SHV-28 and TEM-1 genes, as well as the aminoglycoside resistance gene 16S rRNA methylase rmtF .…”
Section: Discussioncontrasting
confidence: 99%
“…However, this study found that the MIC of imipenem was 2-16mg/L, lower than that of meropenem (4-32mg/L), which may be related to the presence of membrane protein genes (OmpK35/36/37). The antibiotic susceptibility and resistance genes of ST15-type strains reported in the study also differ from previous reports ( Hu et al., 2013 ; Han et al., 2021 ; Zhao et al., 2022 ). Most ST15 OXA-232-producing CRKP strains in previous studies co-produce CTX-M-15 , KPC-2 and NDM-1 , while our strains carry three more AMR genes, including CTX-M-1 , SHV-28 and TEM-1 genes, as well as the aminoglycoside resistance gene 16S rRNA methylase rmtF .…”
Section: Discussioncontrasting
confidence: 99%
“…When analyzed SNPs in 22122315 (ST15), it was compared with recently reported ST15 isolates ( Zhao et al, 2022 ). Considering all SNPs in the coding DNA sequence (CDS) region, we identified 36 common mutations, including 1 stop lost.…”
Section: Resultsmentioning
confidence: 99%
“… Distribution of single nucleotide polymorphisms (SNPs) in hypervirulent isolate 22122315 that causes missense mutations compared to previous ST15 isolates ( Zhao et al 2022 ). Here, presence or absence of missense mutations in CDS region (green), start codon (blue) and stop codon (red) are represented in different colors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations